An unusual early-diverging plesiosauroid from the Lower Jurassic Posidonia Shale of Holzmaden, Germany - Sachs, Sven; Madzia, Daniel (PeerJ, 2025)
The lower Toarcian Posidonia Shale at Holzmaden, Southwest Germany, has yielded some of the most remarkable Lower Jurassic marine tetrapod specimens, including five plesiosaur taxa identified from nearly complete skeletons. This study provides a comprehensive description of an osteologically immature plesiosauroid skeleton found in a Holzmaden quarry in 1978. Despite that the specimen has been researched in the past, previous studies have been either brief or targeted some specific aspects of the specimen, such as its soft tissue preservation. The anatomy and taxonomy of the specimen have never been explored in detail. We reinterpret several of its osteological features and evaluate their taxonomic and phylogenetic significance. Our findings reveal that the specimen possesses an unusual combination of character states, which are not markedly affected by ontogenetic development, warranting the designation of a new taxon, Plesionectes longicollum gen. et sp. nov., thereby increasing the known plesiosaur diversity of both the Toarcian age and the Posidonia Shale.
Keywords: Plesiosauroidea; Plesiosauria; Toarcian; Jurassic; Osteology; Phylogeny reconstruction; Holzmaden; Germany